Implementation of Black Box Testing and Usability Testing on the PPDB Website of YPP Nurul Huda Surabaya - Farhani, Alivia Rahma; Pamungkas, Aji Bayu; Sulistiyani, Endang; Budiarti, Rizqi Putri Nourma (TEKNOLOGI DITERAPKAN DAN JURNAL SAINS KOMPUTER, 2024)
This study aims to evaluate the quality of the PPDB (online student admission) website of YPP Nurul Huda Surabaya using black box testing and usability testing approaches. The black box method was applied to assess the functional performance of the available features, while usability testing was employed to measure user satisfaction using the USE questionnaire. The black box test results indicate that all features operate correctly, and the usability testing produced a score of 0.90, which is close to the ideal value. These findings demonstrate that the website meets the criteria of a well-designed information system and is suitable for use in the PPDB process.